Decentralisation in SADC countries :transformation and challenges of decentralisation - Issa, Abdul-hakim Ameir (University of the Western Cape, 2013)
Magister Legum - LLM === This study focussed on the transformation of the institutions of local government from deconcentration, delegation to devolution. This transformation can be looked at starting with the institutions inherited from the colonial era, which started after the Berlin Conference of 1884, which divided Africa among the western powers. Then the transformation, which took place immediately after independence; that is the period of 1960s, the changes made in the 1980s and finally the transformation taking place following the multiparty democracy in the 1990s. The study looked at decentralisation during the colonial period; decentralisation after independence, with a particular focus on the institutions under a single party system; transformation of local government under multiparty system. It also examined the challenges facing decentralisation in the SADC region. === South Africa